P1383 The effects of doxorubicin on left and right ventricular strain in patients with lymphoma: insights from a retrospective study. (17th January 2020) - Vahabi, S; Stewart, M; Kasim, A; Hancock, H; Norouzi, M; Maddox, J; Austin, D
Abstract: Funding Acknowledgements: South Tees Research and Development Fund (UK) Background: Anthracyclines are a cornerstone in the management of lymphoma. However, their use is associated with cardiotoxicity. Speckle tracking echocardiography (STE) has been established as a valid measure of quantifying cardiac function. However, most studies to this date have focused predominantly on left ventricular (LV) global longitudinal strain (GLS) with only a limited number assessing the right ventricle (RV) and other LV strain parameters. Purpose: Using 2D STE, we assessed the effects of anthracyclines on LV and RV strain parameters, focusing on LV endocardial (GLS), LV myocardial GLS (myoGLS), LV radial strain (GRS), RV endocardial (RV GLS), myocardial GLS (RV myoGLS), and RV free wall strain (RVFWS). Methods: We retrospectively collected data on patients treated for lymphoma between 2015-2018. Two groups (G) were defined: those with a conventional drop in LV ejection fraction (EF), (G1, n = 11) and those without (G2, n = 24). Echocardiograms were performed pre-chemotherapy (T0), mid-treatment (T1), and post-chemotherapy (T2) and were analysed offline using vendor-independent software (TomTec 2D CPA). LV and RV strain analysis was performed in both groups. This study was ethically approved by Health Research Association (REC Reference 18/SS/0139). Results: Mean age was 61 ± 16 years (G1) and 65 ± 12 years (G2). 18% (G1) and 17% (G2) of patients had a history of IHD in each group. Mean cumulative dose of doxorubicin was 280 ± 31 mg/m2 (G1) and 280± 48mg/m2 (G2). In both groups, there was no significant change in LV or RV strain parameters from T0 to T1. In G1, between T1 and T2, patients exhibited a significant deterioration in LV GLS (-19.7 ± 2.6% vs.-15.6 ± 2.5% p < 0.0005), and LV myoGLS (-17.3 ± 2.2% vs. -14.1 ± 2.9% p = 0.02). There was also a measurable decline in RV strain parameters between T1 to T2 (RV GLS, -23.1 ± 4.7% vs. -18.8 ± 4.2% p = 0.028) and (RV myoGLS -21.5 ± 5.2% vs -17.3 ± 3.6% p = 0.013). When analysed from T0 to T2, the changes in RV strain were more marked; RV GLS (-25.2 ± 4.9% vs. -18.8 ± 4.2% p = 0.005), RV myoGLS (-22.4 ± 5.2% vs-17.3 ± 3.6% p = 0.005), and RVFWS (-28.8 ± 5.7% vs. -20.9 ± 6.7% p = 0.001). In G2, no change was observed in LV GLS (-20.4 ± 2.3% vs. -19.6 ± 2.8% p = 0.66), LV myoGLS (-18.8 ± 2.5% vs. -17.5 ± 3.1% p = 0.18), RV GLS (-24.2 ± 2.3% vs. -23.1 ± 2.7% p = 0.42), RV myoGLS (-22.4 ± 2.9% vs. -20.6 ± 2.8% p = 0.09), RVFWS (-26.7 ± 4.6% vs. -25.2 ± 3.6% p = 1.0). GRS did not significantly change in either G1 or G2 during treatment. Conclusion: In patients with a reduction in LVEF, this analysis demonstrated a significant reduction in LV strain parameters secondary to anthracycline treatment. Novel strain parameters did not change in the normal EF group, or predate EF/GLS decline in those with reduced LVEF. Measurable RV dysfunction was noted in those with LV deterioration, highlighting the global cardiac insult of anthracycline treatment. Preventative and monitoring strategies in cardio-oncology should not overlook RV function.